Micropatterned superhydrophobic structures for the simultaneous culture of multiple cell types and the study of cell-cell communication - Efremov, Alexander; Stanganello, Eliana; Welle, Alexander; Scholpp, Steffen; Levkin, Pavel (Biomaterials, 2013)
The ability to control spatial arrangement and geometry of different cell types while keeping them separated and in close proximity for a long time is crucial to mimic and study variety of biological processes in vitro. Although the existing cell patterning technologies allow co-culturing of different cell types, they are usually limited to relatively simple geometry. The methods used for obtaining complex geometries are usually applicable for patterning only one or two cell types. Here we introduce a convenient method for creating patterns of multiple (up to twenty) different cell types on one substrate. The method virtually allows any complexity of cell pattern geometry. Cell positioning on the substrate is realized by a parallel formation of multiple cell-containing microreservoirs confined to the geometry of highly hydrophilic regions surrounded by superhydrophobic borders built-in a fine nanoporous polymer film. As a case study we showed the cross-talk between two cell populations via Wnt signaling molecules propagation during co-culture in a mutual culture medium.
Available online 7 December 2012
Gesehen am 08.01.2021